(untitled) (Balneo and PRM Research Journal, 2024)
Muscle power (FxV, explosive strength or explosive power) is an element of fitness level that influences the quality and efficiency of movements. Most of the studies that address plyometrics identify the effectiveness of this method at the level of performance athletes with different specializations and muscle power requirements. We considered that we can also study the possibility of using plyometrics in physical education lessons. The research identifies the benefits of implementing plyometric exercises for non-athlete university students on lower body muscle power indicators in curricular physical activities. The group of analyzed students (327 subjects/undergraduate level, of which 143 female and 184 male) participated in physical education lessons during one academic year (1 activity per week). The plyometric exercises used were jumping variants, diversified and adapted in dosage to the motor possibilities of the non-athlete students (on one or both legs, lateral, on ladder rungs or boxes, over hurdles, over cones, vertical and horizontal jumps). Their usefulness and effectiveness were verified by 3 successive tests: at the beginning, middle, and end of the academic year, through a battery of 7 lower body muscle power tests. The statistical calculation identifies significant increases in performance for both genders for all tests applied, both between the initial and final tests (T1-T3) and over the shorter time intervals/T1-T2 and T2-T3 (p <0.05). For males, we found greater progress in the second semester of the year (T2-T3) for 5 of the 7 tests, so their adaptation is better and they respond to plyometric training better in the second part of the academic year. For females better progress in semester 2 (T2-T3) for 3 of the tests, respectively greater differences at the end of semester 1 (T1-T2) for 3 tests, especially for endurance power and 10 m acceleration. The research results confirm the effectiveness of plyometric exercises in increasing muscle power indicators for the studied student groups and are a useful option for improving fitness levels. The attractiveness and diversity of the used exercises ensured good student engagement in the lessons. Although the improvements are statistically significant, the results do not indicate spectacular increases and are still weaker than the values recorded in most other research. This is because the students involved in our study are not at all concerned about engaging in leisure time physical activities, except for curricular physical education activities, sedentarism being a major problem among young people.